Application of Mesoporous Silica Nanoparticles in Cancer Therapy and Delivery of Repurposed Anthelmintics for Cancer Therapy - Maedeh Koohi Moftakhari Esfahani; Seyed Ebrahim Alavi; Peter J. Cabot; Nazrul Islam; Emad L. Izake (MDPI AG, 2022)
This review focuses on the biomedical application of mesoporous silica nanoparticles (MSNs), mainly focusing on the therapeutic application of MSNs for cancer treatment and specifically on overcoming the challenges of currently available anthelmintics (e.g., low water solubility) as repurposed drugs for cancer treatment. MSNs, due to their promising features, such as tunable pore size and volume, ability to control the drug release, and ability to convert the crystalline state of drugs to an amorphous state, are appropriate carriers for drug delivery with the improved solubility of hydrophobic drugs. The biomedical applications of MSNs can be further improved by the development of MSN-based multimodal anticancer therapeutics (e.g., photosensitizer-, photothermal-, and chemotherapeutics-modified MSNs) and chemical modifications, such as poly ethyleneglycol (PEG)ylation. In this review, various applications of MSNs (photodynamic and sonodynamic therapies, chemotherapy, radiation therapy, gene therapy, immunotherapy) and, in particular, as the carrier of anthelmintics for cancer therapy have been discussed. Additionally, the issues related to the safety of these nanoparticles have been deeply discussed. According to the findings of this literature review, the applications of MSN nanosystems for cancer therapy are a promising approach to improving the efficacy of the diagnostic and chemotherapeutic agents. Moreover, the MSN systems seem to be an efficient strategy to further help to decrease treatment costs by reducing the drug dose.